A new species of Chlorociboria (Helotiales, Ascomycota) on herbaceous stems from China - Zheng, Huan-Di; Zhuang, Wen-Ying (Phytotaxa, 2017)
A new species, namely Chlorociboria herbicola, is discovered on herbaceous stems in central China. Morphologically, the new fungus is distinctive by the combination of light blue-green apothecia, rectangular cells in ectal excipulum, and elongate-ellipsoidal ascospores with rounded ends. Phylogenetic analyses of the internal transcribed spacer and large subunit of nuclear ribosomal DNA sequences confirm its ascription in Chlorociboria and distinction from the known species of the genus.